Pemahaman dan kemampuan siswa sekolah menengah pertama dalam menulis surat dinas berdasarkan struktur surat - Yulia Nelfita; Yenni Hayati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Teaching materials regarding an official letter of request for permission prepared by students have several mistakes, namely in determining the composition of the official letter. Weak skills in compiling official letters for junior high school (SMP) students are thought to be caused by their low understanding and ability to write official letters. So this study aims to analyze the understanding and ability of junior high school level students in writing official letters. This research method is a quantitative method. The number of samples in this study was 60 students. The research instrument used was the official letter writing test. The results showed that generally, the level of ability to write official letters of students was in the sufficient category. So that there needs to be more special attention from the teacher to improve the understanding and ability of junior high school students in compiling official letters based on the structure of the letter.